Hadith #2700 - Sunan Abi Dawud - Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; ibn Umar; Ibrahim bin Hamza bin Muhammad إبراهيم بن حمزة بن محمد; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
Some slaves (of the unbelievers) went out to the Messenger of Allah (ﷺ) on the day of al-Hudaybiyyah before treaty. Their masters wrote to him saying: O Muhammad, they have not gone out to you with an interest in your religion, but they have gone out to escape from slavery. Some people said: They have spoken the truth, Messenger of Allah, send them back to them. The Messenger of Allah (ﷺ) became angry and said: I do not see your restraining yourself from this action), group of Quraysh, but t
Grade: Sahih

Hadith #4475 - Sunan Abi Dawud - Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
He (the Prophet) commanded regarding the two men and the woman who spoke obscenity were Hassan ibn Thabit and Mistah ibn Uthathah. An-Nufayl said: It is said that the woman was Hammah daughter of Jahsh.
Grade: Hasan

Hadith #5087 - Sunan Abi Dawud - Aban bin 'Uthman أبان بن عثمان بن عفان; Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Nsr bin 'Asim al-Antaky نصر بن عاصم الأنطاكي; Uthman ibn 'Affaan (Sunan Abi Dawud)
If anyone says in the morning: “O Allah! whatever oath I take, whatever word I speak, and whatever vow I take, Thine will precedes all that: whatever Thou willeth, occurs, and whatever Thou dost not will, dost not occur. O Allah! pardon me and disregard me for it. O Allah! whomsoever Thou sendest thine blessing, to him my blessing is due, and whomsoever thou cursest, to him my curse is due, ” exemption from it will be granted to him that day.
Grade: Da'if